2014
DOI: 10.1152/physiolgenomics.00044.2013
|View full text |Cite
|
Sign up to set email alerts
|

Host susceptibility to malaria in human and mice: compatible approaches to identify potential resistant genes

Abstract: Hernandez-Valladares M, Rihet P, Iraqi FA. Host susceptibility to malaria in human and mice: compatible approaches to identify potential resistant genes. Physiol Genomics 46: 1-16, 2014. First published October 29, 2013 doi:10.1152/physiolgenomics.00044.2013.-There is growing evidence for human genetic factors controlling the outcome of malaria infection, while molecular basis of this genetic control is still poorly understood. Case-control and family-based studies have been carried out to identify genes unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 177 publications
(189 reference statements)
0
32
0
Order By: Relevance
“…Host contributions to parasite clearance in malaria impact the duration and severity of the initial infection and so are likely to be lowest early in acute infections in previously unexposed individuals. In rodents, it is possible for different mouse strains to have different MICs because the different inbred mouse strains have different genetic backgrounds [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…Host contributions to parasite clearance in malaria impact the duration and severity of the initial infection and so are likely to be lowest early in acute infections in previously unexposed individuals. In rodents, it is possible for different mouse strains to have different MICs because the different inbred mouse strains have different genetic backgrounds [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…The best examples are the Fulani, who exhibit greater resistance to malaria infection and mild and severe malaria attacks when compared to other sympatric ethnic groups living in the same villages (Modiano et al 1996(Modiano et al , 1998 (Dolo et al 2005) (Bereczky et al 2006. The genetic component of malaria-related phenotypes was also observed by comparing monozygotic twin pairs with dizygotic pairs as well as siblings (Hernandez-Valladares et al 2014). Two studies have evaluated the genetic influence on susceptibility/resistance to malaria, but only small part was attributed to the hemoglobin S (HbS) and -thalassemia genes, suggesting that other genes may be involved on the resistance to P. falciparum malaria (Mackinnon et al 2005;Phimpraphil et al 2008).…”
Section: Host Geneticsmentioning
confidence: 99%
“…Two studies have evaluated the genetic influence on susceptibility/resistance to malaria, but only small part was attributed to the hemoglobin S (HbS) and -thalassemia genes, suggesting that other genes may be involved on the resistance to P. falciparum malaria (Mackinnon et al 2005;Phimpraphil et al 2008). Besides the heritability of malaria phenotypes, many studies have identified genes or genomic regions associated with susceptibility to P. falciparum malaria (Driss et al 2011;Hernandez-Valladares et al 2014). WHO advises the rotational use of these insecticides for indoor residual spraying (IRS).…”
Section: Host Geneticsmentioning
confidence: 99%
See 2 more Smart Citations